BKMI Event Management System using QR Code and Two-Factor Authentication - Thamil Selvam, Harshana; Harun, Nur Ziadah (Applied Information Technology And Computer Science, 2023)
The BKMI event management application addresses the challenges associated with event tracking and information gathering. Currently, there is a significant problem in manually collecting proper data related to events, resulting in a lack of organized information. This makes it difficult to keep track of events, retrieve relevant data efficiently and the process of gathering information on events is time-consuming. This application aims to enhance security and streamline event coordination. The application utilizes QR codes and two-factor authentication (2FA) to improve attendance integrity, prevent fraud, and simplify the check-in process. Additionally, the system incorporates 2FA to add an extra layer of security. Thus, organizations can streamline their event management processes, enhance data accuracy, and save significant time and effort in information gathering.